Electron thermalization and ion acceleration in XUV-produced plasma from nanoparticles in He gas environment - Eva Klimešová; Olena Kulyk; Lucas J Martin; Bernd Schütte; Ulrike Frühling; Markus Drescher; Rui Pan; Nikola Stojanovic; Ivette J Bermudez Macias; Stefan Düsterer; Jakob Andreasson; Marek Wieland; et al. (New Journal of Physics)
We use intense femtosecond extreme ultraviolet (XUV) pulses with a photon energy of 92 eV from the FLASH free electron laser to irradiate substrate-free CsCl nanoparticles surrounded by a He gas with a number density of around 10 ^15   cm ^−3 . By simultaneously detecting electrons and energetic ions from the laser-irradiated micron-size target we study the acceleration mechanism of light ions at the microplasma-vacuum boundary as well as at the layer close to the nanoparticle surface. When the XUV pulse interacts with the gas alone, helium ions are accelerated to energies exceeding 100 eV. In the presence of the nanoparticle, light ions gain additional energy in the electric field around the ionized nanoparticle and their energy spectrum changes considerably. We present an electrostatic model to explain the ion acceleration mechanisms both with and without the nanoparticle and discuss the role of the gas environment in experiments.